Evidence of iguanodontian dinosaurs from the Lower Cretaceous of Tunisia. (May 2016) - Fanti, Federico; Cau, Andrea; Panzarin, Lukas; Cantelli, Luigi
Abstract: The fossil record of ornithischian dinosaurs from Africa is particularly scarce and limited to a few historic localities. In this study we describe new ornithischian remains from the Albian deposits of southern Tunisia (Tataouine Governorate), represented by isolated teeth of large-bodied iguanodontians. Teeth display a wide, diamond-shaped crown with a primary ridge dividing the occlusal surface in two unequal parts and two or more secondary ridges. Hook-like denticles are present on both mesial and distal crown margins and do not display mammillae. In overall morphology, specimens are comparable to those of many Early Cretaceous basal hadrosauriforms, including isolated ornithopodan teeth from comparably-aged levels of Niger. Transversal sections of the crowns permitted identification of dental tissues, which include a thick enamel, and well developed longitudinal and transverse giant tubules. Their relative extents appear to be related to the size, thus developmental age, of the tooth. Teeth are representative of the Oum ed Diab Member, a unit characterized by coastal deposits accumulated under arid to xeric climatic conditions and dominated by fish, crocodilians, and hydraulically transported rebbachisaurid and spinosaurid remains. Sedimentological data and preservation bias strongly support selective taphonomic causes for the fossil distribution of ornithischians in southern Tunisia questioning the purported geographic and paleoecologic distribution of isolated Saharan dinosaurs. Highlights: In this study we describe isolated iguanodontians teeth from the Albian of Tunisia. Teeth occur in the Albian coastal deposits of the Ain el Guettar Formation. Iguanodontians are associated with spinosaurids, rebbachisaurids and crocodilians. Taphonomic analyses challenges paleoecologic distribution of isolated Saharan dinosaurs.